Evolving walkability of major cities in the People's Republic of China - Peilei Fan; Guanghua Wan; Lihua Xu; Hogeun Park; Yaowen Xie; Yong Liu; Wenze Yue; Jiquan Chen (Asian Development Bank Institute (ADBI), 2017)
Context: Walkability is an important element for assessing urban sustainability. There are increased concerns that more cities in the People's Republic of China (PRC) have become less walkable. Objectives: We aim to develop a composite walkability index. We intend to use it to evaluate the spatio-temporal evolution of the walkability of PRC cities in the context of the rapid urbanization. Methods: We developed a comprehensive walkability index that integrates five aspects of the urban built environment: dwelling density, street connectivity, land-use mix, access to public transit, and elevation variation. Using Shanghai, Hangzhou, Chongqing, and Lanzhou as cases, we evaluated the spatio-temporal patterns and changes of walkability in the context of rapid urban expansion. Results: All four cities expanded their urban land from 1990 to 2010, but that there was a higher expansion rate in 2000-2010 than in 1990-2000. For inner cities, Shanghai had the highest average walkability index, whereas Lanzhou held the lowest. In 2000-2010, however, the inner cities of Hangzhou, Chongqing, and Lanzhou and the entire cities of Shanghai and Chongqing increased their walkability index, whereas the inner city of Shanghai had decreased walkability. Furthermore, while inner cities of Shanghai and Hangzhou experienced decreased or stable walkability, inner cities of Lanzhou and Chongqing enjoyed moderate to high increases in walkability. Conclusions: The spatiotemporal changes in walkability seem to be directly associated with governmental policies at both central and local levels. The walkability index method can be widely implemented for any urban landscape because of its comprehensiveness, simplicity, and flexibility.
Keywords: 330; walkability index; urban landscape; dwelling density; street connectivity; land-use mix; public transit; elevation